Photocatalytic C-N coupling from stable and transient intermediates for gram-scale acetamide synthesis - Xin Li; Weiping Yang; Junping Yue; Jieyuan Li; Shujie Shen; Ruimin Chen; Jielin Wang; Huimin Dan; Dagang Yu; Fan Dong (Nature Communications)
Abstract Electro/photocatalytic C-N coupling acts as a key build-block to the next generation of chemicals like amides for wide applications in energy, pharmaceuticals and chemical industries. However, the uncontrolled intermediates coupling challenges the efficient amide production regarding yield or selectivity. Here we propose a photocatalytic radical addition route, where the fundamental active species, including oxygen and photogenerated electron-hole pairs, are regulated for selective intermediates generation and efficient acetamide synthesis from mild co-oxidation of CH3CH2OH and NH3. Sufficient CH3CH2OH is provided to accumulate the stable intermediate (CH3CHO). Meanwhile, the limited NH3 concentration ensures the controllable generation and fast addition of the transient radical (●NH2) on CH3CHO. Through the directed coupling of stable-transient intermediates, the acetamide synthesis rate is pushed forward to a hundred-mmol level (105.61 ± 4.86 mmol·gcat −1·h−1) with a selectivity of 99.17% ± 0.39%, reaching a gram-scale yield (1.82 g) of acetamide. These results illuminate valuable opportunities for the photocatalysis-driven synthetic industry.